2010
DOI: 10.1111/j.1525-139x.2010.00757.x
|View full text |Cite
|
Sign up to set email alerts
|

Epicardial Cardiac Rhythm Devices for Dialysis Patients: Minimizing the Risk of Infection and Preserving Central Veins

Abstract: Transvenous leads of cardiac rhythm devices (CRDs) are known to cause central stenosis and are vulnerable to contamination during hemodialysis access-related bacteremia. In this retrospective study, nine consecutive chronic hemodialysis patients with transvenous CRD infection due to dialysis access-related bacteremia and recurrent central stenosis are presented. Four patients with tunneled hemodialysis catheters (TDCs) and three with arteriovenous grafts experienced access-related bacteremia that spread to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
67
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 37 publications
1
67
0
Order By: Relevance
“…After neck movements, oral secretions may contaminate the dressing. Another potential problem associated with temporary catheterization is vein stenosis (18), particularly when the jugular site is chosen in the presence of pacemaker leads (19). After colonization of the central catheter, the pacemaker leads can also become infected (20).…”
Section: Discussionmentioning
confidence: 99%
“…After neck movements, oral secretions may contaminate the dressing. Another potential problem associated with temporary catheterization is vein stenosis (18), particularly when the jugular site is chosen in the presence of pacemaker leads (19). After colonization of the central catheter, the pacemaker leads can also become infected (20).…”
Section: Discussionmentioning
confidence: 99%
“…Recently published preliminary information lends validity to the epicardial approach in HD patients. In this study, the development of CIED infection and central stenosis were markedly reduced after the endocardial devices were removed and replaced with epicardial CIEDs [31]. Bardy et al reported recently that subcutaneous ICD consistently detected and converted spontaneous and induced VF [36].…”
mentioning
confidence: 80%
“…Repeated cannulation of arteriovenous fistulas and the use of tunneled catheters for HD are potential sources for bacteremia in this population. The intravascular location of the CIEDs makes the leads vulnerable to bacterial seeding during HD [31]. In recent years, we have also observed an evolution of implantation techniques of epicardial and subcutaneous CIEDs, making it accessible to patients in whom the traditional transvenous implantation could be associated with high complication rates [32][33][34][35][36].…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…Most studies comparing the value of epicardial versus transvenous CIED lead placement have been conducted in patients from the general population in whom transvenous leads had been removed because of infection. Efficacy and mortality were usually equal in both groups [19, 20]. However, placement requires cardiothoracic surgery, which is an expensive procedure.…”
Section: Discussion/conclusionmentioning
confidence: 99%